Whitewashing American Exceptionalism: Racialized Subject-Positioning and US Foreign Policy - Maass, Richard W (International studies quarterly, 2024)
Abstracts American exceptionalism is enjoying a revival of scholarly interest amid new approaches to studying foreign policy narratives and unease regarding how US policymakers will manage a less unipolar international system. That revival coincides temporally, though not yet substantively, with growing attention to racialized dynamics and Eurocentrism within international relations. This article examines how core strands of American exceptionalism—the prevailing narrative framing of US foreign policy—reflect a whitewashed understanding of US foreign policy that can best be understood as the product of racialized subject-positioning that saturated its historical development. After conceptualizing American exceptionalism, it develops a theoretical framework to capture how racialized subject-positioning stratifies understandings of a nation’s role in the world. It proceeds to investigate how this process shaped the development of American exceptionalism in line with epistemologies of immanence, ignorance, and innocence, producing exceptionalist narratives that neglect non-white populations as meaningful others in the construction of US national identity and that negate US interactions with those groups as relevant evidence that might undercut its exceptionalism. These whitewashing effects remained embedded even as overtly racist discourse became delegitimized, posing enduring obstacles for US diplomacy today.